(untitled) (Scientific journal of the Fergana State University, 2023)
Language is the most important tool that humanity can have.We express our thoughts and convey information to each other through language. Without language, without this weapon, we can not only express our views, but also we can not build the elements that are the basis of our development and growth. Therefore, it is no exaggeration to say that language is developing through different societies and civilizations around the world.Although language learning itself is a very interesting process, special attention should be paid to language learning, because it is a property of particular societies and the process of language development and evolution. Language is a reflection of culture in society and its perception of the world; as it transmits information, it shows how a particular society receives, processes, evaluates, and sends this information. The development of a particular language over time shows how the society or societies that use it develop over time, and changes in cultural outlook, social composition, and political conditions profoundly affect the language’s characteristics.